Fisheries Information Systems in the Mediterranean. Current state and the need for integration - Papaconstantinou C.; Conomou A.; Kavadas S. (Dynamique des populations marines, 1998)
The introduction of Integrated Fisheries Information Systems for the Mediterranean is proposed. a first step for the integration is to establish a Mastertable providing information on the existing national statistics of the different segments of the fishing industry. Next, items liable to integration at the Mediterranean level have to be decided. The structure, nature, quality profile and available time series of existing national statistic systems are reviewed, and summarized information concerning aspects of integration for each segment of the fishing industry is presented.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)